Research on Reservoir Characteristics and Main Controlling Factors of Longwangmiao Formation of Cambrian in Sichuan Basin - Wang, Qiang; Wang, Xingzhi; Zeng, Xinyao (Frontiers in Earth Science, 2022)
Based on the 4 measured profiles, 17 observation profiles, and 13 drilling core macroscopic and microscopic characteristics of the Cambrian Longwangmiao Formation in the Sichuan Basin, combined with analysis and testing, and reservoir logging interpretation, the reservoir characteristics and main controlling factors of the Longwangmiao Formation are analyzed. The marginal bank of the underwater paleo-uplift of the restricted platform and the point bank facies within the platform belong to the sedimentary facies belts that are most conducive to the formation and evolution of the reservoir. However, the later transformation of dolomitization and dissolution played decisive roles in the formation of the reservoir. The Caledonian epigenetic karstification is the main reason for the lack of the overlying stratum of the Cambrian in the Sichuan Basin, and it is also the most important factor for the formation of large-scale dissolved cavities in the Longwangmiao Formation in the Sichuan Basin.